Multimodality Imaging in the Diagnosis and Staging of Gestational Choriocarcinoma - Mandava, Anitha; Koppula, Veeraiah; Kandati, Meghana; Reddy, Arvind K.; Rajappa, Senthil J.; Rao, T. S. (Indian Journal of Radiology and Imaging, 2024)
Choriocarcinoma is an uncommon, highly invasive malignancy arising from the placental trophoblastic tissue. Though staging is clinical, imaging has significant role in the diagnosis, staging, prognostic risk scoring, and management of choriocarcinomas. The purpose of this article is to review the role of multimodality imaging in the diagnosis, staging, and management of choriocarcinomas in correlation with clinicopathologic findings.
Keywords: choriocarcinoma; ultrasound; color Doppler; computed tomography; positron emission tomography; magnetic resonance imaging